Self-Esteem and Social Media Addiction among College Students: Contribution Gender as Moderator - Wahyuni, Esa Nur; Maksum, Ali (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1153, 2020)
Social media has become an important part of the life of college students and is an addiction to social media, so there is a risk of success for college students. Although still controversial, self-esteem is suspected as a predictor of social media addiction behavior. This study examines the effect of selfesteem on social media addiction and how does the power of selfesteem influence if it is moderated with gender? A total of 225 students from 4 universities have been respondents in this study. The instrument used for data collection, namely the Rosenberg self-esteem scale, was developed by Rosenberg (1965) to measure the level of self-esteem. While Social Media Addiction used to measure addiction behavior of social media. The Social Media Addiction developed by Sahin. Data were analyzed by moderator regression analysis. The results of study point out that self-esteem significantly not relationship to social media addiction. In addition, gender variable also has a moderator function, which is to strengthen the relationship of self-esteem variables on social media addiction.